Migration capital: theoretical, conceptual and pragmatic aspects (World of finance, 2019)
Introduction. A clear understanding ofthe patterns ofthe formation, distribution and use of migration capital is impossible without a thorough theoretical and methodological developments, taking into accounthistoricalparallels and studying advanced foreign experience in this held.Purpose. Investigation of the essence and theoretical generalization of the definition of “migration capital”, analysis ofthe current practice ofthe arrival of migration capital to individual countries of the world and Ukraine, as well as the development of proposals for the implementation of effective measures forits use.Results. Theterm “migration capital” is relatively new in modem financial science. Many domestic scholars and foreign researchers identifythe concept ofmigration capital and remittances ofiabormi-grants. According to our convictions, money transfers to migrant workers are private transfers of crisislike nature, which are sent voluntarily by labor migrants to specific households in order to maintain their financial stability. Thus, we can argue that transfers of money transfers, in essence, form a separate component ofthe international capital market - migration capital.Conclusion. Money remittances of migrant workers are essentially a migration capital. The development of financial infrastructure, the use of state-of-the-art money transfer technologies, and the improvement and expansion of banking services in the area ofservicing remittances of migrant workers will adequately address the financial potential ofmigration capital, which in turn will stimulate economic and social developmentofthe country.